Thermal challenges in lithium-ion battery technology: Investigating performance and thermal stability - Kenza Maher (22803425) (2025)
Due to their remarkable energy density and prolonged lifespan, lithium-ion batteries (LiB) are indispensable in various applications, such as energy storage systems and electric vehicles. However, ensuring the safety and reliability of these batteries in desert environments presents significant challenges due to high temperatures, pervasive dust, and limited cooling mechanisms. Elevated temperatures exacerbate internal resistance and accelerate chemical reactions within the battery, leading to heat generation, performance loss, and potential safety risks, including thermal runaway. This study investigates the thermal challenges in LiB technology, focusing on the performance and degradation of lithium cobalt oxide (LCO) and graphite full cells under prolonged cycling at elevated temperatures of 55 °C. Results show a significant reduction in discharge capacity, decreasing from 38.12 mAh in the first cycle to 24.36 mAh after 350 cycles at 55 °C, corresponding to a 36.1 % capacity loss. This degradation at 55 °C after 350 cycles mirrors the capacity loss observed at 25 °C after 1000 cycles, illustrating the accelerated effects of higher temperatures. Open circuit voltage (OCV) profiles and entropy measurements reveal notable variations and phase transitions in the cells' internal properties, especially around specific states of charge (SOC) and OCV regions. These findings underscore the critical role of temperature in the aging process and highlight the necessity of effective temperature control and management to optimize the lifespan and performance of lithium-ion batteries in high-temperature environments. Other Information Published in: Journal of Energy Storage License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.est.2025.115396